2011
DOI: 10.1037/a0021929
|View full text |Cite
|
Sign up to set email alerts
|

Attention, exposure duration, and gaze shifting in naming performance.

Abstract: Two experiments are reported in which the role of attribute exposure duration in naming performance was examined by tracking eye movements. Participants were presented with color-word Stroop stimuli and left-or right-pointing arrows on different sides of a computer screen. They named the color attribute and shifted their gaze to the arrow to manually indicate its direction. The color attribute (Experiment 1) or the complete color-word stimulus (Experiment 2) was removed from the screen 100 ms after stimulus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 75 publications
(178 reference statements)
1
27
1
Order By: Relevance
“…Naming RT is longer in the incongruent than in the neutral condition and often shorter in the congruent than in the neutral condition (for reviews, see MacLeod, 1991; Roelofs, 2003). In line with the RTs, participants gaze longer at incongruent than neutral stimuli and longer at neutral than congruent stimuli (Roelofs, 2011), which suggests that there are differences in attention demand among the Stroop conditions. Greater attentional effort is often reflected in a higher skin-conductance response, which is observed for the incongruent compared with the congruent Stroop condition (Naccache et al, 2005).…”
Section: Evidence That Word Planning Requires Central Attentionmentioning
confidence: 62%
See 2 more Smart Citations
“…Naming RT is longer in the incongruent than in the neutral condition and often shorter in the congruent than in the neutral condition (for reviews, see MacLeod, 1991; Roelofs, 2003). In line with the RTs, participants gaze longer at incongruent than neutral stimuli and longer at neutral than congruent stimuli (Roelofs, 2011), which suggests that there are differences in attention demand among the Stroop conditions. Greater attentional effort is often reflected in a higher skin-conductance response, which is observed for the incongruent compared with the congruent Stroop condition (Naccache et al, 2005).…”
Section: Evidence That Word Planning Requires Central Attentionmentioning
confidence: 62%
“…In line with this, Roelofs (2007) observed that participants gaze longer at picture–word stimuli in the semantically related than unrelated condition. Similarly, gaze durations depend on the amount of conflict in the color–word Stroop task (Roelofs, 2011). In a commonly used version of the Stroop task, participants name the color attribute of colored congruent or incongruent color–words (e.g., the words GREEN or RED in green ink, respectively; say “green”) or neutral series of Xs.…”
Section: Evidence That Word Planning Requires Central Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the arrows < and > were flanked by two Xs on each side. Pretests for the present experiments and previous work using the same paradigm (Roelofs, 2007(Roelofs, , 2008a(Roelofs, , 2008b(Roelofs, , 2011 revealed that participants cannot discriminate the arrow while fixating the Stroop stimulus. This is also demonstrated by Figure 2, where fixating the Stroop stimulus precludes discrim ination of the arrow, even though Stroop stimulus and arrow are much closer to each other than 24°.…”
Section: Estimating the Onset Of Articulatory Bufferingmentioning
confidence: 87%
“…Roelofs, 2007Roelofs, , 2008aRoelofs, , 2008bRoelofs, , 2011, as illustrated in Figure 2. Colors were presented as colored rectangles, and incongruent words or Xs were superim posed onto these rectangles.…”
Section: Experim Entmentioning
confidence: 98%